The Opacity Indebted - Morales Salazar, Rodrigo (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
Text articulated in three movements: the first, reviews the possibility of thinking the poem as access, debt and exaction, based on the writings of Jean-Luc Nancy, especially in his essay "Do, the poetry." The second moment is related to thinking the poem in connection with the violence that constitutes it.  And finally, we approach the thought of Maurice Blanchot, to inquire about the close link between poem and disaster.
Keywords: poem; debt; exaction; access; disaster; violence